Risk Analysis of Supply Chain in the Construction of Power Plant Barge Using Failure Mode and Effect Analysis (FMEA) Method - Timbul Guntoro; Intan Baroroh; Basuki Widodo; Ali Azhar (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Power Plant Barge is a Barge / Barge that functions as a Power Plant with the ability to produce 60 MW of electricity production and has the mobility to be moved from one place to another with a towing system using a Tugboat. The purpose of this research is to analyze supply chain risks in the procurement process that affect the delay in ship construction. This research is to complement previous research that has analyzed the Production process. From the research results, the number of risk events can be identified. A questionnaire was prepared to determine the risk weight using the Failure Mode and Effect Analysis (FMEA) method. There are how many risk events with a high Risk Priority Number (RPN) that affect the delay in barge construction. The results showed an assessment score in the form of a Risk Priority Number (RPN) consisting of activities: The calculation of the estimated material list is revised due to the minimum order with a score of 235.98, The length of the engineering evaluation process (Evatek) with a score of 275.99, Shipping Documents are often sent late by importers with a score of 262.00 and material status is still Eigen Loosing with a score of 169.13. Develop a mitigation strategy to prevent the risk from recurring. There are 8 mitigation steps that can be taken based on the results of discussions with expert practitioners in the shipping industry as described in Table 4.17 regarding developing mitigation strategies such as seeking data from manufacturers regarding minimum orders for steel plates and profiles, coordination with suppliers regarding manufacturing data during Engineering evaluation, Shipping and Customs processes and receipt of materials must be faster, so that potential delays to the shipbuilding process can be avoided.